1970
DOI: 10.1007/bf00387173
|View full text |Cite
|
Sign up to set email alerts
|

Oligomycin effect on ion absorption by excised barley roots and on their ATP content

Abstract: Chloride absorption by excised barley roots from dilute solutions is more oligomycin-sensitive than its absorption from more concentrated solutions and than K(+) and Na(+) absorption from dilute as well as concentrated solutions. Oligomycin decreased the ATP content of excised barley roots. The mode of oligomycin interference with ion absorption by plant cells is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1970
1970
1982
1982

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The inhibition increases with increasing oligomycin concentration, and the oligomycin concentration giving 50%o inhibition is about 6 (6) show that oligomycin inhibits Cl-influx more than K+ influx in excised barley roots. Lin and Hanson (7) showed that oligomycin inhibits phosphate influx in corn roots to a greater extent than can be accounted for by its effect on ATP levels, and Malone et al (8) …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The inhibition increases with increasing oligomycin concentration, and the oligomycin concentration giving 50%o inhibition is about 6 (6) show that oligomycin inhibits Cl-influx more than K+ influx in excised barley roots. Lin and Hanson (7) showed that oligomycin inhibits phosphate influx in corn roots to a greater extent than can be accounted for by its effect on ATP levels, and Malone et al (8) …”
Section: Resultsmentioning
confidence: 90%
“…Disks about 0.8 mm thick and 4 mm diameter were cut from storage tissue of red beet (Beta vulgaris L.), and washed in 0.1 mm aerated CaSO4, changed daily, at 22-24 C. The washing was continued for [5][6][7] days, except where otherwise indicated, in order to allow development of Cl-transport (12 15,000g. Eight-ml samples of supernatant + 10 ml Aquasol (New England Nuclear) were counted in a scintillation counter, and then recounted for 36C1 after decay of the 42K.…”
mentioning
confidence: 99%
“…Histochemical techniques have been used to localize ATPases at cell membranes (13,14,26,28,32), and correlations between salt-stimulated ATPase activity and ion absorption have been established (8)(9)(10). Support for the view that ATP levels govern ion absorption by roots is found in several reports (3,6,(18)(19)(20)24 (Tables III and V).…”
Section: Resultsmentioning
confidence: 92%
“…The final reaction volume was 3.0 ml and consisted of 25 [LM NADH, 25 ltM cytochrome c, 0.167 mm KCN, and 50 mm KH2PO4, pH 7.6. The reaction was run at room temperature, about 24 C. Enzyme concentration was chosen to give an optical density change of less than 0.1 unit/min (about 20 pg protein). The reaction was initiated by the addition of substrate.…”
mentioning
confidence: 99%
“…The external Rb+ concentrations studied were in the range of 1 to 50 mM. (17,19,20) in roots, it would seem that ATP could also serve as the actual energy source for transport. In green algae it has been concluded that anion transport is more closely linked to the photosynthetic electron transport process whereas cation transport is coupled to ATP formation and utilization (25,30,31).…”
mentioning
confidence: 99%